Non-linear analysis on stability of corrugated cross-ply laminated composite plates - Bich, Dao Huy; Phu, Khuc Van (Vietnam Journal of Mechanics, 2006)
In the present paper the governing equations for corrugated cross-ply laminated composite plates in the form of a sine wave are developed based on the Kirchoff-Love’s theory and the extension of Seydel’s technique. By using Bubnov-Galerkin method approximated analytical solutions to the non-linear stability problem of corrugated laminated composite plates subjected to biaxial loads are investigated. The post buckling load-deflection curve of corrugated plates and analytical expressions of the upper and lower buckling loads are presented. The effectiveness of corrugated plates in enhancing the stability compared with corresponding fiat plates is given